Interfacing Neural Network Components and Nucleic Acids - Lissek, Thomas (Frontiers in Bioengineering and Biotechnology, 2017)
Translating neural activity into nucleic acid modifications in a controlled manner harbours unique advantages for basic neurobiology and bioengineering. It would allow for a new generation of biological computers that store output in ultra-compact and long-lived DNA and enable the investigation of animal nervous systems at unprecedented scales. Furthermore, by exploiting the ability of DNA to precisely influence neuronal activity and structure it will be possible to create biomedical cellular prostheses to treat psychiatric diseases for which currently no adequate therapies exist.